Reviewing Guidelines on Diabetic Retinopathy Screening in Children and Adolescents with Type 1 Diabetes: Is there consistency amongst practitioners? - Xiaoke Li, Katherine; Lovell, Marge; Evans, Keira; Gallego, Patricia H (Canadian Journal of Optometry, 2015)
Diabetic retinopathy (DR) is a common eye disease and a leading cause of visual impairment in patients with Type 1 diabetes (T1DM). Retinopathy screening for T1DM varies according to the age of disease onset and diabetes duration. Retinal screening varies from standard fundal examination to more advanced methods of screening. An online survey was conducted in February 2014. The purpose of this survey was to assess the frequency and methods of eye examinations routinely performed in children and adolescents with T1DM. Data on local practices were collected from a group of optometrists and ophthalmologists in the London-Middlesex area. One hundred and one surveys were e-mailed out and the response rate was 37.6%. Results indicated that different screening methods vary according to individual practices. These results may have an impact on the findings of retinopathy in this population. A review of utilized screening methods and comparisons to established guidelines will be highlighted.